Laparoscopic Repair of Combined Right Diaphragm and Liver Injuries with a Sharp Object: A Case Report. (9th December 2013) - Arık, M. Kasım; Tas, Sükrü; Özkul, Faruk; Şahin, Hasan; Karatağ, Ozan; Karaayvaz, Muammer
Abstract : Introduction . Diaphragm injuries develop following penetrating or blunt traumas. The purpose of the case report is to present a 28 year old male patient with stable hemodynamic findings treated with laparoscopic approach following a liver injury combined with a right diaphragm injury caused by a sharp penetrating object. Case . 4 cm long transverse laceration was observed near the middle axillary line in the 6th right intercostal space in the examination performed on a 28 year old male patient who applied to the emergency service due to sharp penetrating object injury. Respiratory sounds were decreased in the right side and the examination revealed sensitivity in the abdomen. Elevation in the right diaphragm and hemopneumothorax was monitored in chest X-ray and computerized tomography. Closed subaqueous thorax drain was placed and the patient was taken to the surgery with a right diaphragm injury prediagnosis. Laparoscopic exploration was performed to the patient with stable hemodynamic findings by entering through 10 mm port above the abdomen. 6 cm long injury at the right side of diaphragm and approximately 2 cm deep at the deepest point and 5 cm long linear laceration was observed in the 7th segment of the liver. The diaphragm was repaired laparoscopically with sutures that do not melt on their own. Tampon was applied to the laceration in the liver and bleeding control was performed with suture. Patient was discharged on the 3rd day because he had no problems during postoperative follow-ups. Result . No noticed right side diaphragm rupture and possible concomitant visceral organ injuries following a penetrant injury that can cause significant mortality and morbidity should be definitely kept in mind. The detection of right side diaphragm and liver injury is vital with high mortality in case of delayed diagnosis, and direct radiography and computerized tomography are helpful in the diagnosis. Surgical treatment with laparoscopic approach is a method that leads to less hospitalization duration and less pain in cases that are hemodynamically stable.